Chinese Families Upside Down: Intergenerational Dynamics and Neo-Familism in the Early 21st Century - Yunxiang Yan (Brill, 2021)
Chinese Families Upside Down offers the first systematic account of how intergenerational dependence is redefining the Chinese family. The authors make a collective effort to go beyond the conventional model of filial piety to explore the rich, nuanced, and often unexpected new intergenerational dynamics. Supported by ethnographic findings from the latest field research, novel interpretations of neo-familism address critical issues from fresh perspectives, such as the ambivalence in grandparenting, the conflicts between individual and family interests, the remaking of the moral self in the face of family crises, and the decisive influence of the Chinese state on family change. The book is an essential read for scholars and students of China studies in particular and for those who are interested in the present-day family and kinship in general.